A numbering-up strategy of hydrodynamic microfluidic filters for continuous-flow high-throughput cell sorting. Issue 10 (18th April 2019) - Ozawa, Ryoken; Iwadate, Hideki; Toyoda, Hajime; Yamada, Masumi; Seki, Minoru
Abstract : A numbering-up strategy of hydrodynamic filters was presented to dramatically increase the throughput of cell/particle sorting up to ∼15 mL min −1 . Abstract : Even though a number of microfluidic systems for particle/cell sorting have been proposed, facile and versatile platforms that provide sufficient sorting throughput and good operability are still under development. Here we present a simple but effective numbering-up strategy to dramatically increase the throughput of a continuous-flow particle/cell sorting scheme based on hydrodynamic filtration (HDF). A microfluidic channel equipped with multiple branches has been employed as a unit structure for size-based filtration, which realizes precise sorting without necessitating sheath flows. According to the concept of resistive circuit models, we designed and fabricated microdevices incorporating 64 or 128 closely assembled, multiplied units with a separation size of 5.0/7.0 μm. In proof-of-concept experiments, we successfully separated single micrometer-sized model particles and directly separated blood cells (erythrocytes and leukocytes) from blood samples. Additionally, we further increased the unit numbers by laminating multiple layers at a processing speed of up to 15 mL min −1 . The presented numbering-up strategy would provide a valuable insight that is universally applicable to general microfluidic particle/cell sorters and may facilitate the actual use of microfluidic systems in biological studies and clinical diagnosis.